Associative political culture in the Holy Roman Empire: the Upper Rhine, c. 1350-1500 - Hardy, D (2015)
Historians have long struggled to conceptualise the Holy Roman Empire in the later middle ages. This thesis seeks to provide an interpretation of political life in the Empire which captures the structures and dynamics in evidence in the sources. It does so through a comparative study of the varied socio-political elites along the Upper Rhine between 1350 and 1500, with frequent reference to other regions of the Empire. The thesis is divided into three sections. Part I, consisting of four chapters, examines the shared and interconnective characteristics of several spheres of activity – the documentary, judicial, ritual, military, and administrative – in which various elites interacted through the same practices and conventions. Part II (five chapters) deals with the types of contractual association which emerged organically from these shared and interconnective structures and practices. It shows that these associations – leagues, alliances, judicial agreements, coinage unions, and others – were more common and more similar than typically assumed, that they regulated key judicial and military affairs, and that they reflected a shared ideology which emphasised peace-keeping and the common good within the Empire’s framework. Part III of the thesis shows how the structures and dynamics explored in Parts I and II played out in specific situations by reference to three case studies in the 1370s-'80s, 1410s-'30s, and 1460s-'70s. All three demonstrate how the 'associative political culture' model can illuminate events which were previously considered to be moments of crisis or chaos, or the products of 'territorial' or 'constitutional' processes. The thesis concludes by arguing that, in light of this evidence, the Holy Roman Empire is best understood as a community of interdependent elites who interacted within a shared 'associative political culture'. This conclusion highlights the need for a new paradigm beyond those of the 'territory', the 'constitution', or the centralising 'state'.